ANALISIS PENGARUH DIGITAL MARKETING, ONLINE COSTUMER REVIEW TERHADAP KEPERCAYAAN KONSUMEN DAN KEPUTUSAN PEMBELIAN (STUDI PADA ASN PENGGUNA TIKTOK SHOP DI BATURAJA) - Thamrin, Thamrin; Munajat, Munajat; Fifian Permata Sari (LPSDI Bina Patria, 2025)
This study aims to analyze the influence of Digital Marketing and Online Customer Reviews on Consumer Trust and Purchasing Decisions of State Civil Apparatus (ASN) users of TikTok Shop in Baturaja. Using quantitative research methods, data were collected from 200 respondents through a structured questionnaire. The variables studied include Digital Marketing, Online Customer Reviews, Consumer Trust, and Purchasing Decisions. The validity and reliability of the research instrument were tested, and a classical assumption test was conducted to ensure the suitability of the regression model. The results of the study indicate that Digital Marketing has a significant and positive effect on Consumer Trust and Purchasing Decisions. Online Customer Reviews have a significant effect on Purchasing Decisions but do not have a significant effect on Consumer Trust. In addition, Purchasing Decisions partially mediate the relationship between Digital Marketing and Consumer Trust, although the mediation effect is not statistically significant. The results also show the important role of Digital Marketing in building Consumer Trust and driving Purchasing Decisions on the TikTok Shop platform. These findings provide practical implications for businesses looking to optimize marketing strategies through digital platforms and leverage customer reviews to increase consumer engagement and trust. Future research is recommended to explore additional variables that may influence this relationship.